Volatility-resolved source apportionment of primary and secondary organic aerosol over Europe. (October 2017) - Skyllakou, Ksakousti; Fountoukis, Christos; Charalampidis, Panagiotis; Pandis, Spyros N.
Abstract: A three-dimensional regional chemical transport model (Particulate Matter Comprehensive Air Quality Model with Extensions, PMCAMx) was applied over Europe combined with a source apportionment algorithm, the Particulate Source Apportionment Technology (PSAT), in order to quantify the sources which contribute to the primary and secondary organic aerosol (OA) during different seasons. The PSAT algorithm was first extended to allow the quantification of the sources of OA as a function of volatility. The most significant OA sources during May were biogenic, while during February residential wood combustion and during September wildfires dominated. The contributions of the various sources have strong spatial dependence. Wildfires were significant OA sources (38% of the OA) for Russia during September, but had a much lower impact (5%) in Scandinavia. The above results are in general consistent with the findings of the CARBOSOL project for selected sites in Europe. For remote sites such as Finokalia in Crete, more than 90% of the OA has undergone two or more generations of oxidation for all seasons. This highly processed oxidized OA is predicted to also dominate over much of Europe during the summer and fall. The first generation SOA is predicted to represent 20–30% of the OA in central and northern Europe during these photochemically active periods. Highlights: Spatial and seasonal contributions of OA sources in Europe are quantified. Biogenic sources dominate in early summer. Residential wood combustion is important during winter. Wildfires are major sources in early fall. Highly processed OA dominates over much of Europe during summer and fall.